CREATIVE CITIES AND TERRITORIES: THE CASE OF THE QUADRILATERAL ASSOCIATION IN NORTHERN PORTUGAL, A RELATIONSHIP UNDER CONSTRUCTION - Cortez, Maria Raquel; Teixeira, Luís (Brazilian Creative Industries Journal, 2022)
Collaborative work between cities is pointed out to confer dimension and competitiveness to cities or territories that cooperate in networks. Despite some discussion about the advantages and disadvantages of investing in creative cities and territories, there are numerous examples where this investment is associated with sustainable and inclusive development. The purpose of this article is to present the journey of Quadrilateral Association as a reflection on how the implementation of creative cities and territories can lead to greater territorial cohesion and a regional commitment to innovation and creativity as development factors. First, it is referred the origins of the Urban Quadrilateral Association for Competitiveness, Innovation, and Internationalization in the North of Portugal and the territorial context in which it is located. Afterwards, the article addresses the work carried out in the four municipalities that constitute it, Barcelos, Braga, Famalicão, and Guimarães. Finally, it ends with an overview of the challenges that remain.